Association Between Kinetics of Early Biofilm Formation and Clonal Lineage in Escherichia coli - Saskia-Camille Flament-Simon; Marion Duprilot; Marion Duprilot; Noémie Mayer; Vanesa García; María Pilar Alonso; Jorge Blanco; Marie-Hélène Nicolas-Chanoine; Marie-Hélène Nicolas-Chanoine (Frontiers in Microbiology, 2019)
BackgroundEscherichia coli biofilm formation has mostly been assessed in specific pathogenic E. coli groups. Here, we assessed the early biofilm formation (EBF), i.e., adhesion stage, using the BioFilm Ring Test® on 394 E. coli clinical isolates (EC) [196 consecutively isolated (CEC) in 2016 and 198 ESBL-producing E. coli (ESBLEC) isolated in 2015]. Then, biofilm-forming ability was contrasted with phylogroups, clonotypes (fumC-fimH), and sequence types (STs), all being used to define clones, virulence factors (VF), and FimB.ResultAccording to both biofilm production levels at 2, 3, and 5 h, and EBF kinetics over 5 h, CEC and ESBLEC isolates segregated into three EBF groups: strong (G1), moderate (G2), and weak (G3) producers. At 2 h, strong producers were more frequent among CEC (n = 28; 14.3%) than among ESBLEC (n = 8; 4%) (P = 0.0004). As CEC and ESBLEC isolates showed similar individual EBF kinetics in each group, a comparison of isolate features between each group was applied to gathered CEC and ESBLEC isolates after 2 h of incubation, 2 h being the most representative time point of the CEC and ESBLEC isolate segregation into the three groups. Phylogroup B2 displayed by 51.3% of the 394 isolates was more frequent in G1 (77.8%) than in G3 (47.6%) (P = 0.0006). The 394 isolates displayed 153 clones, of which 31 included at least three isolates. B2-CH14-2-ST127, B2-CH40-22-ST131, B2-CH52-5/14-ST141, and E-CH100-96-ST362 clones were associated with G1 (P < 0.03) and accounted for 41.7% of G1 isolates. B2-CH40-30-ST131 clone was associated with G3 (P < 0.0001) and accounted for 25.5% of G3 isolates. VF mean was higher among G1 than among G3 isolates (P < 0.001). FimB-P2 variant was associated with G1 (P = 0.0011) and FimB-P1 variant was associated with G3 (P = 0.0023). Clone, some VF, and FimB were associated with EBF, with clonal lineage being able to explain 72% of the variability of EBF.ConclusionAmong our 394 isolates, <10% are able to quickly and persistently produce high biofilm levels over 5 h. These isolates belong to a few clones previously described in various studies as dominant gut colonizers in mammalians and birds and comprised the B2-CH40-22-ST131 clone, i.e., the ancestor of the globally disseminated B2-CH40-30-ST131 clone that is the dominant clone among the weak biofilm producers.